Appropriateness of the definition of 'sedentary' in young children: Whole-room calorimetry study. Issue 5 (September 2015) - Reilly, John J.; Janssen, Xanne; Cliff, Dylan P.; Okely, Anthony D.
Abstract Objectives The present study aimed to measure the energy cost of three common sedentary activities in young children to test whether energy expended was consistent with the recent consensus definition of 'sedentary' as 'any behaviour conducted in a sitting or reclining posture and with an energy cost ≤1.5 metabolic equivalents (METs)' (Sedentary Behaviour Research Network, 2012). Design Observational study. Methods Whole-room calorimetry measures of television viewing, sitting at a table drawing and reading, and sitting on the floor playing with toys were made in 40 young children (mean age 5.3 years, SD 1.0). Results The energy cost of each sedentary activity was consistent with the recent consensus definition of sedentary: 1.17 METs (95% CI 1.07–1.27) for TV viewing; 1.38 METs (95% CI 1.30–1.46) for sitting at a table; and 1.35 METs (95% CI 1.28–1.43) for floor-based play. Conclusions Common sedentary activities in young children have energy costs which are consistent with the recent consensus definition of 'sedentary', and the present study is supportive of this definition.